Students' adaptation strategies in coping with homesickness: a qualitative systematic review - Amelia, Resa; Kholidin, Farid Imam (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
Homesickness is a psychological condition commonly experienced by migrant students, characterized by a deep longing for home, family, and familiar surroundings. This study aims to analyze the adaptation strategies employed by students in coping with homesickness. The method used is a Systematic Literature Review (SLR) of ten articles indexed in Scopus, sourced from reputable databases such as Elsevier, Emerald, Springer, and Taylor and Francis, published between 2020 and 2025. The findings indicate that students apply various coping strategies, including problem-focused and emotion-focused approaches. They also rely on social support, engage in campus activities, and maintain active communication with their families as efforts to overcome homesickness. These findings highlight the importance of social, cultural, and institutional factors in the adaptation process. This research provides significant contributions to the development of guidance and counseling programs in higher education institutions to support students experiencing homesickness.